Social economy and new business models in the media sector. The case of the street paper Shedia - Papadopoulou, Lambrini (The Greek Review of Social Research, 2023)
This article explores the new business models that are emerging organically in the Greek media landscape and which over and above economic goals prioritize social values and visions that are consistent with the principles of social economy, such as the fight against exclusion and the reintegration and empowerment of vulnerable social groups. Focusing on the field of social economy, it aims to record and research the alternatives that can emerge when the third sector meets the media sector. Through the analysis of the business model of the street magazine Shedia, this article argues that social economy can lay the foundations for a new media model that has the potential to create powerful ruptures in the dominant paradigm.